Amphiphilic zinc phthalocyanine photosensitizers: synthesis, photophysicochemical properties and in vitro studies for photodynamic therapy1. Issue 20 (28th May 2015) - Çakır, Dilek; Göksel, Meltem; Çakır, Volkan; Durmuş, Mahmut; Biyiklioglu, Zekeriya; Kantekin, Halit
<x xml:space="preserve">Abstract</x> Peripherally and non-peripherally tetra-substituted zinc(ii) phthalocyanines bearing 2-(2-2-[3-(dimethylamino)phenoxy]ethoxyethoxy)ethoxy and 2-(2-2-[3-(diethylamino)phenoxy]ethoxyethoxy)ethoxy groups (2a, 5a, 3a and 6a) were synthesized by cyclotetramerization of the corresponding phthalonitriles (2, 5, 3 and 6).